RECEPTION OF SOCIAL LEGAL CONSCIENCE IN SOCIAL-PHILOSOPHICAL THEORIES OF THE MODERN AGE - Орденов, С. С. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article represents social-philosophical reconstruction of legal conscience in the epoch of the Modern Ages.